The Influence of Used WhatsApp Group in Online Learning to Student Discipline at Elementary School - Mukhasin, Mukhasin; Andriani, Ana (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Abstract. The background of this study is the low attitude of student discipline during distance learning. This study aims to determine the benefits of WhatsApp groups in distance learning on improving the discipline attitude of elementary school students. Student discipline is very important to improve learning outcomes. The data used is secondary data, as well as the research method used is literature study research. The analysis technique used in this study is the content analysis. The data obtained will be collected, analyzed, and concluded to get the expected conclusion. Based on the results of literature research from several journals written by researchers previously showed that the use of WhatsApp groups in distance learning is very useful in the process of increasing student discipline.